Risk analysis of electronic transactions in tourism web applications - Bidart, Ruhan; Silveira, Lucas Maia; Pereira, Adriano César Machado; Veloso, Adriano Alonso (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
line sales, mainly due to agility to buy and attractive prices that are offered on the Web. However, fraud has also been increased on the same rate or more. In order to address this problem it is very important to understand the characteristics of fraudsters and their typical behavior. On the tourism e-market it is not different, thus millions of frauds occur each year. In this work we analyze a representative amount (thousands) of online transactions of a tourism Web system. We try to understand the characteristics of fraudsters with the main goal to support decision of e-payment evaluation of transactions. Our results are promising, achieving up to 64% of increase in accuracy in comparison to the baseline.